Dynamic characteristics of cerebrovascular reactivity or ventilatory response to change in carbon dioxide. Issue 9 (5th August 2020) - Ogoh, Shigehiko; Shibata, Shigeki; Ito, Go; Miyamoto, Tadayoshi
Abstract : New Findings: What is the central question of this study? What are the dynamic characteristics of cerebrovascular carbon dioxide reactivity and the central respiratory chemoreflex? What is the main finding and its importance? The transfer function gain from the end‐tidal partial pressure of carbon dioxide to cerebral blood flow or ventilation decreased in the high frequency range at rest and during exercise. These findings indicate that the dynamic characteristics of both systems were not constant in all frequency ranges, and this trend was not modified by exercise. Abstract: The purpose of this study was to examine the dynamic characteristics of cerebrovascular reactivity and ventilatory response to change in arterial CO2 in all frequency ranges at rest using frequency domain analysis, and also to examine whether this is modified by dynamic exercise as with the traditionally determined cerebrovascular CO2 reactivity. In nine healthy young subjects, at rest and during exercise (cycling exercise at constant predetermined work rate corresponding to a V ̇ O 2 level of 0.90 l min −1 ), the dynamic characteristics of cerebrovascular CO2 reactivity and the central respiratory chemoreflex were assessed by transfer function analysis using a binary white‐noise sequence (0–7% inspired CO2 fraction) from the end‐tidal partial pressure of CO2 ( P ETC O 2 ) to the mean middle cerebral artery mean blood velocity (MCA V m ) or minute ventilation ( V ̇ E ), respectively. In the high frequency range, both transfer function gains decreased but, interestingly, the cut‐off frequency in the transfer function gain from P ETC O 2 to MCA V m response was higher than that from P ETC O 2 to V ̇ E response at rest (0.024 vs . 0.015 Hz) and during exercise (0.030 vs . 0.011 Hz), indicating that cerebrovascular CO2 reactivity or central respiratory chemoreflex was not constant in all frequency ranges, and this trend was not modified by exercise. These findings suggest that dynamic characteristics of the cerebrovascular CO2 reactivity or central chemoreflex need to be assessed to identify the whole system because the traditional method cannot identify the property of time response of these systems. Abstract :